OCCURRENCE OF THE PENAEID PRAWN PENAEUS JAPONICUS BATE IN HOOGHLY ESTUARY - Nandi, N C; Das, S R; Chatterjee, J G (Indian Journal of Fisheries, 2011)
A male specimen of Penaeus japonicus Bate caught off Sagardwip, Sunderbans, is reported, being the second report on its occurrence so far from the east coast of India.